Preparation of bivalent agonists for targeting the mu opioid and cannabinoid receptors - Dvorácskó Szabolcs (EUROPEAN JOURNAL OF MEDICINAL CHEMISTRY, 2019)
In order to obtain novel pharmacological tools and to investigate a multitargeting analgesic strategy, the CB1 and CB2 cannabinoid receptor agonist JWH-018 was conjugated with the opiate analgesic oxycodone or with an enkephalin related tetrapeptide. The opioid and cannabinoid pharmacophores were coupled via spacers of different length and chemical structure. In vitro radioligand binding experiments confirmed that the resulting bivalent compounds bound both to the opioid and to the cannabinoid receptors with moderate to high affinity. The highest affinity bivalent derivatives 11 and 19 exhibited agonist properties in [35S]GTPγS binding assays. These compounds activated MOR and CB (11 mainly CB2, whereas 19 mainly CB1) receptor-mediated signaling, as it was revealed by experiments using receptor specific antagonists. In rats both 11 and 19 exhibited antiallodynic effect similar to the parent drugs in 20 μg dose at spinal level. These results support the strategy of multitargeting G-protein coupled receptors to develop lead compounds with antinociceptive properties. © 2019 Elsevier Masson SAS